Optimization of ultrasound and enzyme assisted extraction of eurycomanone from eurycoma longifolia (tongkat ali) - Yuhai, He (2018)
Eurycomanone extraction from E. longifolia is conventionally done using decoction method, but most times, the product quality, yield, and extraction duration are not ideal. Exposure to unfavorable process conditions usually results in the formation of product metabolites. To address these problems, the alternative extraction methods that increases the product yield ought to be investigated. In this study, several approaches, including ultrasound and enzyme-assisted methods were studied. Different parameters for the extraction process were screened using OFAT and optimized using FCCCD of RSM. The conventional method of decoction and Soxhlet were studied for eurycomanone extraction, and decoction was found of better performance which gives eurycomanone yield of 0.237 %. The Soxhlet extraction achieved a significant model while the process wasn’t able to be optimized because of the degradation of the final product due to the high temperature employed in Soxhlet system. Thus, decoction was used as the control for indicating that if the use of ultrasound, laccase and cellulase could make a better yield of eurycomanone. The methods studied for the extraction of eurycomanone are ultrasound-assisted extraction, cellulase enzyme-assisted extraction, laccase enzyme-assisted extraction, cellulase enzyme-laccase enzyme combined extraction, laccase enzyme-ultrasound combined extraction, cellulase enzyme-ultrasound combined extraction, cellulase enzyme-laccase enzyme-ultrasound combined extraction. Ultrasound-assisted extraction gives optimum eurycomanone yield of 0.294 %; Cellulase enzyme-assisted makes optimum eurycomanone yield of 0.20 %; Laccase enzyme-assisted extraction makes optimum eurycomanone yield of 0.215 %; Cellulase-laccase enzyme makes optimum eurycomanone yield of 0.176 %; Cellulase enzyme-ultrasound combined extraction makes optimum eurycomanone yield of 0.152 %; Laccase enzyme-ultrasound combined extraction makes optimum eurycomanone yield 0.190 %; Cellulase-laccase-ultrasound combined extraction makes optimum eurycomanone yield of 0.193 %. The ultrasound-assisted extraction method yielded the highest eurycomanone (0.294%) which was mainly due to disruption of the cell wall by the cavitation formation and collapse of the sonication process. The enzyme assisted extraction didn’t show a better extraction, however, it is remarkable that the use of laccase made the extraction period shortened to 1h which same as the time used by the ultrasound assisted extraction. Thus, in consideration of time saving in the extraction, laccase enzyme-assisted extraction should also be considered even though its yield is not as high as ultrasound-assisted extraction. SEM studies revealed a considerable effect of the extraction processes on the surface of the substrates. All the extraction processes had considerable effects on the solid material but the effects of ultrasound assisted extraction were more pronounced. In conclusion, the use of ultrasound assisted methods for the extraction of eurycomanone from E. longifolia could be considered effective and friendly approaches.